The Effectiveness Differences of Adlerian Group Play Counseling and Classroom Guidance Activity in Improving Interpersonal Attractiveness - Fajar Bilqis; Agus Taufiq; Ipah Saripah (Universitas Ahmad Dahlan, 2017)
This study was aimed at generating the empirical data on the effectiveness difference between Adlerian Group Play Counseling (AGPC) intervention and classical guidance service in improving interpersonal attractiveness based on the social relationship profile. This study was categorized as an experimental study with factorial design. The sample of this study comprised the fifth-grade students of Sukasenang Elementary School and Cihaurgeulis Elementary School. Interpersonal attractiveness questionnaire and sociometry emerged as the instruments of this study. The data were analyzed by using two-way analysis of variance. The result of this study demonstrated that AGPC intervention was more effective than the classroom guidance activity in improving all interpersonal attractiveness categories. The school counselor may utilize the result of this study as an alternative strategy to improve students’ interpersonal attractiveness.